Portal sobre ginecomastia - Amato, Fernando Campos Moraes [UNIFESP] (2016)
Introduction: Gynecomastia is the growth of breast tissue in men. The prevalence is higher in puberty and may even reach 65% in the age range of 14 to 15 years, and only in 7.5% of the pacients persists after 17 years. Surgery for gynecomastia correction corresponds almost 10% of all plastic surgeries performed on men. In adolescence can regresses in most times, however, at this stage, this physical change may interfere with the self-esteem and quality of life of the patient, and also difficult interpersonal relationships, compromising the development of the individual. The causes of gynecomastia are differents, sometimes can be symptom of a severe disease, in addition has many different treatments. The lack of information and guidance of these patients becomes more an aggravating factor for the diagnosis and management. Objective: Develop a free internet portal to inform the general population about gynecomastia. Method: Anteriority research was conducted on the most used internet search engines (Google® and Yahoo®). Domain was registered according to the proposal, hosted on webserver and installed Drupal® 7 software for website management. Content creation was made with easily understanding language and use bibliografic reference. Input stream analysis and profile of visitors could be made by Google Analytics®. Result: With only two months of publication, and no disclosure to date, the site had more than 250 visits. 81% of entry for Brazilian public. It is visited by more than 10 different countries, even though in Portuguese. Over 70% of visitors found the site organically by google search engine. Conclusion: The Internet proved to be a promising tool as a means of dissemination on various topics involving gynecomastia.